2018
DOI: 10.1080/16549716.2018.1445333
|View full text |Cite
|
Sign up to set email alerts
|

Implications of healing power and positioning for collaboration between formal mental health services and traditional/alternative medicine: the case of Ghana

Abstract: Background: Many current debates about global mental health have increasingly called for collaboration between biomedical and traditional medical health systems. Despite these calls, not much has been written about the variables that would influence such collaboration. To a large extent, collaboration dialogues have considered biomedicine on the one hand, and a wide range of traditional and faith-based treatments on the other hand. However, this dualistic bifurcation does not reflect the plurality of healing s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(44 citation statements)
references
References 35 publications
1
37
0
Order By: Relevance
“…Some studies suggested that service users experience some challenges financing the cost of medication [ 31 , 33 , 35 , 49 , 50 , 52 ]. For instance, whilst the cost of mental health treatment is subsidised for service users [ 49 , 50 , 53 ], they are expected to purchase their own medication from a private pharmacist whenever there is shortage of such drugs at the psychiatric facilities.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies suggested that service users experience some challenges financing the cost of medication [ 31 , 33 , 35 , 49 , 50 , 52 ]. For instance, whilst the cost of mental health treatment is subsidised for service users [ 49 , 50 , 53 ], they are expected to purchase their own medication from a private pharmacist whenever there is shortage of such drugs at the psychiatric facilities.…”
Section: Resultsmentioning
confidence: 99%
“…Research continues to explore traditional healers' understanding of mental illness and suicidal behaviour, yet the effectiveness of their prevention strategies remains largely untested (Bantjes, et al, 2018). Recent research has highlighted the huge diversity in traditional treatment methods; further research must explore the effectiveness and quality of these treatments before they can be recommended or formally integrated (Kpobi & Swartz, 2018).…”
Section: Regulation and Evidence Base Of Traditional Healingmentioning
confidence: 99%
“…Due to the complex nature of indigenous healing in each country, it is unlikely that one single best practice model will be developed that can be followed and implemented across all LMICs. A recent study by Kpobi and Swartz (2018) has emphasised this need for a nuanced approach to collaboration. They clearly demonstrated that different groups of traditional healers exhibit varying perceptions of their own power and ideological proximity to biomedicine; these factors may impact on their motivation for, and understanding of, collaboration; thus traditional healers should not be conceived as one homogeneous group (Kpobi & Swartz, 2018).…”
mentioning
confidence: 99%
“…A study in Malawi among people with epilepsy indicated that they sought both traditional and modern medicine to treat their condition [13]. Other countries in Africa face this multiplicity of health providers like in Ghana [14] South Africa [15] and Ethiopia [16,17]. It has been noted that biomedical treatment offered at health facilities is not adequate.…”
Section: Discussionmentioning
confidence: 99%